The Effect of Individual Counseling on the Improvement of Knowledge and Attitudes of Women of Childbearing Age about SADARI in the Work Area of the UPT Puskesmas Butong Central Kalimantan - Herlina Diatric; Rani Safitri (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2025)
Breast Self-Examination (BSE/SADARI) is a practical and effective approach for the early identification of breast cancer, with the potential to reduce mortality rates by approximately 25–30%. Women who have limited Adequate understanding of breast cancer and Breast Self-Examination (BSE) necessitates appropriate health education beginning in adolescence. This study sought to assess and examine changes in the knowledge and skills of Women of Childbearing Age (WCA/WUS) in performing BSE before and after health education at the Butong Community Health Center, Central Kalimantan. This research employed an analytical survey design. The findings demonstrated a substantial improvement in participants’ knowledge of BSE, increasing from 21% in the good category during the pretest to 83% in the good category after the intervention. Prior to the educational session, 98% of WUS were unable to perform BSE correctly; however, following counseling, 95% were able to carry it out properly. The Wilcoxon test yielded a significance value of 0.000 (p < 0.05), indicating that the counseling intervention had a statistically significant impact on both knowledge and practical ability related to BSE. Therefore, collaboration among village authorities, healthcare providers, and the community is strongly recommended to routinely conduct educational programs in order to enhance awareness and skills in the early detection of breast cancer.